The val66met (rs6265) polymorphism in the brain-derived neurotrophic factor (BDNF) Gene and its potential association with stress levels and haematological parameters - Hatamleh, Mohammad Ahmed Issa
The Brain-Derived Neurotrophic Factor (BDNF) is an important protein which plays a vital role to promote survival of neurons via regulation of the growth and maintenance of nerve cells. Lack of BDNF in the central nervous system is modified by variousbrain stressful conditions. The Valine/Methionine polymorphism at codon 66 (VaI66Met) of the BDNF gene plays a significant role in genetic predisposition to stress in different populations, with Met-allele being more significant; that is related to least expression of BDNF protein, which is in tum associated with increased stress levels. The stressful lifestyle of preclinical medical students increases their stress levels, which was hypothesised to cause certain body responses. These include variety of neurochemical and morphological modifications, such as oxidative stress¬the most common among them. Subsequently, oxidative stress leads to alteration in haematological parameters. This alteration could vary as per genotypic characterization of the Val66Met polymorphism in the BDNF gene via affecting the oxidative stress pathways. This study aimed to determine the allelic and genotypic association of the Val66Met (rs6265) polymorphism in the BDNF gene with the level of stress and to assess the trends in haematological parameters in preclinical medical students of Universiti Sultan Zainal Abidin (UniSZA). This study has obtained ethical approval from UniSZA Human Research Ethics Committee (UHREC), as a cross¬sectional study involving all the 122 preclinical medical students (66 from year I and 56 from year 2).). The validated depression anxiety stress scales-21 (DASS-21) questionnaire was distributed in both English and Bahasa Melayu languages, and blood samples were collected at the same time at UniSZA Medical Clinic for assessing the Complete Blood Count (CBC). Genotyping analysis of the BDNF gene (VaI66Met) polymorphism was then performed by using optimised Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method. A total of 109 students consented to be in the study, but 105 subjects stayed after four were excluded. The results showed that the stress among students were correlated with depression and anxiety (p<O.OI). The Indian students were significantly more likely to have Val/Val genotype whereas Malay students were more likely to have Met/Met genotype (p= 0.027). The three BDNF genotypes (VaiN ai, Val/Met and Met/Met) differed significantly with perceived stress level (p= 0.0 I O); the students who carried Val/Val genotype (mean= 10.6) perceived signi ficantly lower stress than those students who carried Val/Met genotype (mean= 14) and Met/Met genotype (mean= 15.1), respectively. Those students with Val/Met genotype (mean= 13.4) had significantly greater haemoglobin concentration (p= 0.044) than those with MetIMet genotype (mean= 12.1). There was a significant difference in the results of mean corpuscular haemoglobin concentration (MCHC) across their BDNF genotypes (p= 0.036); the students with Val/Val genotype (mean= 31.93) had significantly greater MCHC, than those students with Met/Met genotype (mean= 31.02) and Val/Met genotype (mean= 31.87). There was a significant negative association between stress and white blood cell (WBC) count (p= 0.05). The stress levels and mean platelet volume (MPV) were significantly correlated (p<O.OS), as with the platelet large cell ratio (P-LCR) (p= 0.048). To the best of our knowledge, this is the first study investigating this global issue. The findings from this study should trigger more investigators to focus on the impact of stress and oxidative stress on haematological parameters under potential of genes.